Bottom trawling in sponge grounds of the Barents Sea (Arctic Ocean): A functional diversity approach. (May 2022) - Colaço, A.; Rapp, H.T.; Campanyà-Llovet, N.; Pham, C.K.
Abstract: In the Barents Sea, extensive aggregations of sponges are known to occur, especially in the southwestern portion dominated by large species of Geodia spp. The distribution of deep-sea sponge grounds, considered vulnerable marine ecosystems, often coincides with high fishing efforts targeting demersal fish species and benthic invertebrates using bottom trawls. The aim of this study was to investigate the effects of bottom trawling on the abundance of habitat forming Geodia spp., and on the size composition of Geodia barretti together with functional and species diversity of associated fauna. Using images collected by a Remotely Operated Vehicle, we compared two locations with contrasting levels of trawling effort. We found significantly smaller Geodia barretti in the intensely trawled area as well as differences in species and functional diversity between the two sites. This study provided clear evidence that bottom trawling significantly alter sponge associated communities, significantly reducing the abundance and size of geodiid sponges, and creating a shift in functional diversity. The effects of bottom trawling on Geodia barretti and Geodia spp. grounds are noticeable and results should be used in conservation and management of these diverse sponge grounds. Highligths: Bottom trawling affects the abundance of geodiid sponges We found significantly smaller Geodia barretti in the intensely trawled area Bottom trawling alters sponge associated communities Bottom trawling creates a shift in functional diversity